Composting with Cullunghutti: Experimenting with How to Meet a Mountain. Issue 2 (2nd April 2020) - Turner, Bethaney; Somerville, Wendy
ABSTRACT: To contribute to ongoing efforts to move beyond colonial and anthropocentric modes of knowing, being and doing, this article reflects on experimental endeavours to meet a Mountain—Cullunghutti in New South Wales. We do this by reflecting on the theoretical approaches that informed our modes of engaging with, and attempts to represent, multispecies and multisensorial encounters with the Mountain. Guided by an anticolonial and "compost-ist" ethic, we outline and interrogate our research efforts to develop a framework to enable us to attune our bodies with this multifaceted, more-than-human place and its past, present and speculative future. What we find is that the liveliness of the Mountain resists efforts to "know it", instead inviting us to meet with it in multiple, open and agile ways that unsettle and fragment the hyper-separation of humans from more-than-humans. We identify the concept of composting as a generative mode of representation and research method capable of supporting practices of mutual inclusion that can move across temporal, species and ontological boundaries. In so doing, we highlight the necessity of transgressing discrete disciplinary boundaries to encourage uptake of collaborative and cooperative research that challenges binaries, resists reifying particular forms of knowing, and works towards recuperative futures.